Feasibility Study on Establishment of Po-tea-to Veggies at SM Savemore Market Novaliches, General Luis St., Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Po-tea-to Veggies began on September 23, 2019 and is located at SM Savemore Market Novaliches, General Luis St., Novaliches, Quezon City. Po-tea-to Veggies has four employees, that is, the store manager, one cashier, one service crew, and one kitchen crew. Po-tea-to Veggies’s start-up is Php 1,250,000.00 and is equally divided by each partner. Po-tea-to Veggies offers a unique style of fried potato plate with different flavors of vegetables, combined with different flavors of milk tea all in one cup. Po-tea-to Veggies is designed to easily hold the snack and take it anywhere. Po-tea-to Veggies’s owners conceptualized a business that offers something new and has benefits to the customer. This study utilized a descriptive method of research and financial statement to determine if the business will be applicable in the proposed place. Results of the survey showed that 94% of people around the area are willing to visit the location, most of which are students, workers, shoppers, and commuters. The results of the financial statement showed that the income of the business will increase up to 5% yearly. The researchers should focus on people’s stress, struggles, and problems with their work or studies. The newest product of Po-tea-to Veggies with a twist will convince anyone to drink and eat every day instead of buying a milk tea only at a high price. The tea comes with a fried potato plate in a shape that looks similar to a small plate mixing with healthy flavors of vegetables such as broccoli, carrot, spinach, cauliflower, sweet potato, etc. covered with toppings, such as cheese powder, sour cream, and barbeque. The product is better than French fries. The researchers recommended that the owner should enhance the business proposal to make it more feasible by continuously innovating nutritious products that will benefit the customer. The researchers also recommended promoting the business by using social media advertisement and create more strategies that will help the business become successful.
Keywords: feasibilitystudy, Po-tea-to Veggies